Measuring the impact of some macroeconomic variables on economic stability indicators A comparative study of several countries from 1991 to 2021 - Benlahbib, Taha; Cherayett, Fairouz (The journal of contemporary issues in business and government, 2023)
The purpose of this study was to assess the impact of some macroeconomic variables on indicators of economic stability for a sample of randomly selected countries from 1991 to 2021. To accomplish this, static and dynamic panel models were used to identify various theoretical concepts, previous studies, and the experimental approach. The Panel vector autoregressive (PVAR) model was estimated using the Generalized method of moments (GMM) for the economic growth indicator, and the PARDL model was estimated using the Pooled Mean Group (PMG) and Mean Group (MG) methods for the remaining indicators. In addition to the preference for estimating MG over estimating PMG under certain conditions, the study concluded that there is a positive significant effect between the variables under study in the sample countries and that the fixed effects model is appropriate. Thus, macroeconomic variables can be said to positively affect indicators of economic stability by increasing economic growth rates and lowering general price levels in exchange for lower unemployment rates and thus achieving balance at the level of the balance of payments.